Role of macrophages in in vitro induction of T-helper cells. - Erb, P; Feldmann, M (1975)
In a set of experiments it was ascertained that macrophages incubated in the presence of antigen, for example, keyhole limpet hemocyanin (KLH), can release factor(s) able to induce specific helper cells to KLH. Supernatant taken from purified macrophages, which had been incubated with KLH for 4 days, adequately replaced macrophages and antigen when tested in the helper system. Thus in this system no direct contact between macrophages and T lymphocyte is necessary. Moreover, the supernatant raised from allogeneic (BALB/c) macrophages were ineffective, whereas that derived from F1 macrophages activated helper cells; and that obtained from syngeneic macrophages incubated in the presence of KLH had no effect, even in high doses. By contrast, the latter supernatant was effective if used with a particulate antigen, KLH bound to agarose, suggesting the existence of different mechanisms of helper cell activation by soluble and particulate antigens. Moreover, the supernatant from allogeneic macrophages had the capacity to induce helper cells, if tested in the presence of KLH bound to agarose.